Foraging for water by MIZ1-mediated antagonism between root gravitropism and hydrotropism - Yuzhou Zhang; Zhulatai Bao; Adrijana Smoljan; Yifan Liu; Huihui Wang; Jiří Friml (Proceedings of the National Academy of Sciences, 2025)
Root system integrates multiple environmental cues, chiefly gravity and soil humidity, to anchor plants in soil and forage for water. While the mechanism of auxin-mediated root gravitropism is comparably well-understood, the root’s capability to grow toward moist soil for water uptake and drought avoidance, termed root hydrotropism, remains largely mysterious. Here, we provide key insights into the mechanism of hydrotropic growth and assign a role to the master regulator of hydrotropism, MIZU-KUSSEI 1 (MIZ1). We show that efficient hydrotropism requires the attenuation of antagonistically acting gravitropism, which is inhibited under drought conditions. Drought stress interferes with subcellular trafficking and the lateral mobility of PIN auxin transporters, which are polarly localized at the root cell plasma membranes. This leads to defects in PIN2 polarity and gravity-induced polarization of PIN3, ultimately inhibiting gravity-induced auxin redistribution and root bending. The miz1 mutant is defective in all these regulations, and in support of MIZ1’s action on PINs, pin mutations rescue the hydrotropic defects in the miz1 mutant. These observations identify a mechanism for how drought via MIZ1 attenuates gravitropism to promote root hydrotropism for efficient water foraging under drought conditions.